Government performance accountability: The role of IT, internal control, performance-based budgeting, and organizational commitment - Putri, Ayu Septiana (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2025)
This quantitative study analyzes the effect of utilizing information technology, government internal control system, and performance-based budgeting on government agency performance accountability with organizational commitment as moderating variable. From the population of State Civil Apparatus (ASN) within all Regional Apparatus Organizations (OPD) of Pekalongan City in 2023, 350 respondents were selected as sample using convenience sampling. The type of data collected is primary data obtained through questionnaires. Structural Equation Modeling-Partial Least Square (SEM-PLS) is the data analysis method. This study shows that utilizing information technology, government internal control system, and performance-based budgeting positively and significantly affect government agency performance accountability. Meanwhile, organizational commitment does not moderate the effect of utilizing information technology, government internal control system, and performance-based budgeting on government agency performance accountability.